Standard deviation of carotid young's modulus and presence or absence of plaque improves prediction of coronary heart disease risk. (22nd March 2016) - Niu, Lili; Zhang, Yanling; Qian, Ming; Xiao, Yang; Meng, Long; Zheng, Rongqin; Zheng, Hairong
Summary: Introduction: The stiffness of large arteries and the presence or absence of plaque are associated with coronary heart disease (CHD). Because arterial walls are biologically heterogeneous, the standard deviation of Young's modulus (YM‐std) of the large arteries may better predict coronary atherosclerosis. However, the role of YM‐std in the occurrence of coronary events has not been addressed so far. Therefore, this study investigated whether the carotid YM‐std and the presence or absence of plaque improved CHD risk prediction. Methods: One hundred and three patients with CHD (age 66 ± 11 years) and 107 patients at high risk of atherosclerosis (age 61 ± 7 years) were recruited. Carotid YM was measured by the vessel texture matching method, and YM‐std was calculated. Carotid intima‐media thickness was measured by the MyLab 90 ultrasound Platform employed dedicated software RF‐tracking technology. Results: In logistic regression analysis, YM‐std (OR = 1·010; 95% CI = 1·003–1·016), carotid plaque (OR = 16·759; 95% CI = 3·719–75·533) and YM‐std plus plaque (OR = 0·989; 95% CI = 0·981–0·997) were independent predictors of CHD. The traditional risk factors (TRF) plus YM‐std plus plaque model showed a significant improvement in area under the receiver‐operating characteristic curve (AUC), which increased from 0·717 (TRF only) to 0·777 (95% CI for the difference in adjusted AUC: 0·010–0·110). Conclusions: Carotid YM‐std is a powerful independent predictor of CHD. Adding plaque and YM‐std to TRF improves CHD risk prediction.